Synthesis of Novel Dinaphthosulfide,Aza, Oxa, Thia Lariats ContainingUrea and Thiourea Groups in the Side Chain and Their Nanostructures - E. Rostami; A. Zare (E-Journal of Chemistry)
Dinaphhosulfide aza, oxa, thia crown was prepared; its urea and thiourea derivatives were synthesized by the reaction with ethyl and 4-chlorophenyl isocyanate, ethyl and phenylisothiocyanate. Self-assembled structures are as micro and nano fibers and discs.